2005
DOI: 10.1057/palgrave.mel.9100141
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Modelling of Ship-Berth Link With Priority Service

Abstract: Simulation of the logistics activities related to the arrival, berthing, service and departure processes of ships in container ports can be carried out for different goals such as design of ship-berth link, increase productivity and efficiency of quay cranes, analysis and planning of operations at the ship-berth link, etc. These logistics activities are particularly complex and very costly since they require the combined use of expensive infrastructure capacities especially berths and quay cranes. Ship-berth l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 14 publications
0
17
0
5
Order By: Relevance
“…Berthing of a vessel apart from its desired berthing position misc Miscellaneous Lai and Shih (1992), Legato and Mazza (2001), Henesey et al (2004), and Dragovic et al (2005Dragovic et al ( , 2006. Papers containing ideas and results published elsewhere, for example Kim (2005) and Crainic and Kim (2007), are also excluded.…”
Section: Handling Time Attribute Fixmentioning
confidence: 99%
“…Berthing of a vessel apart from its desired berthing position misc Miscellaneous Lai and Shih (1992), Legato and Mazza (2001), Henesey et al (2004), and Dragovic et al (2005Dragovic et al ( , 2006. Papers containing ideas and results published elsewhere, for example Kim (2005) and Crainic and Kim (2007), are also excluded.…”
Section: Handling Time Attribute Fixmentioning
confidence: 99%
“…According to Dragovic et al (2005), the interarrival time distribution is a basic input parameter that has to be presumed or inferred from observed data. In literature, The processing times at berth for each ship were assumed to be normally distributed and their means are also given in Table 2 Since the container terminal is relatively small, with only two berths, another simplification in the SBL model was taken.…”
Section: Multirio Container Terminalmentioning
confidence: 99%
“…In such cases, the use of simulation as a planning tool has been of growing importance to find a balance between queue priorities and the possibility to postpone such investments. Dragovic et al (2005), who have reported on several different simulation models with respect to port operations, particularly examined the impact of introducing priority for a certain class of ships on SBL performance. One of their simulation models indicated that assigning priority to smaller ships would lead to an improvement of the main operational parameters, like the average number of ships in queue and the average time a ship spends in queue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many studies conducted at container terminals, but many of these studies focus either only on the berth side (e.g., Bierwirth and Meusel, 2009;Dragovic et al, 2005;Imai et al, 2007;Monaco and Sammarra, 2007;Moorthy and Teo, 2006;Razman and Khalid, 2000) or only on the yard side (e.g., Chen, 1999;Chen et al, 2004;Han et al, 2008;Kim and Kim, 2002;Kim and Park, 2003;Kim et al, 2008;Legato et al, 2009;Ma and Hadjiconstantinou, 2008;Zhang et al, 2003). The complexity and dynamic nature of the container terminal operations resulted in difficulties in using analytical tools as the method of investigation.…”
Section: Literature Reviewmentioning
confidence: 99%